Non-invasive bioluminescence imaging of β-cell function in obese-hyperglycemic [ob/ob] mice. - Manishkumar Patel; Alexa Gleason; Stacey O'Malley; Brett Connolly; Donna Suresch; John Virostko; Neil Phillips; Shu-An Lin; Tsing-Bau Chen; Michael Klimas; Richard J Hargreaves; Cyrille Sur; et al. (PLoS ONE)
Background Type 2 diabetes results from failure of the β-cells to compensate for increased insulin demand due to abnormal levels of metabolic factors. The ob/ob(lep-/-) mouse has been extensively studied as an animal model of type 2 diabetes. Previous studies have shown a correlation between β-cell function and bioluminescent imaging in lean genetically engineered mice. The ability to noninvasively monitor β-cell function in ob/ob mice could provide new information on β-cell regulation in type 2 diabetes. Methods To create the B6 Albino ob/ob MIP-luc mice (ob/ob-luc), the ob/ob mouse was crossed with the CD1 MIP-luc mouse. All mice were backcrossed over multiple generations to ensure the genetic background of the transgenic mice was over 96% similar to the background of the original ob/ob mouse. Animal weight, blood glucose levels, insulin in plasma, and in vivo bioluminescence (BLI) were monitored weekly or biweekly for up to 70 weeks of age. BL imaging was performed using IVIS Spectrum (Perkin Elmer) and calculated by integrating the bioluminescence signal between 5 and 10 min after i.v. injection of D-luciferin. Insulin immunohistochemistry determined islet beta cell count and insulin secretion assay determined islet insulin function. Results There were significant increases in BLI and insulin levels as the ob/ob-luc mice aged while glucose levels gradually decreased. Ob/ob-luc were sacrificed at different time points to determine ex vivo BLI, islet function and total β-cell numbers using a cell counting training algorithm developed for the Vectra image analysis system (Perkin Elmer). The number of β-cells increased as the mice aged and all three ex vivo measurements correlated with BLI. Conclusions The ob/ob-luc mice can serve as a model of metabolic stress, similar to human type 2 diabetes using BLI as a surrogate marker for β-cell function.